Public life in the National Museum of Mexico, based on the press from the capital, 1825-1851 (Tzintzun, Revista de Estudios Históricos, 2016)
he National Museum of Mexico was founded in 1825 as part of a series of publiccultural institutions that the newly born nation needed. he collectionsfound in the museum during the irst 30 years of its existence were NaturalHistory, Antiquities, History and Industrial Products. Between 1825 and1851, men-of-letters from the capital supported public collections throughnewspapers and magazines and gave room to public debate on the role of themuseum in Mexican society, as well as initiated a discussion on the criteria ofhow the heritage should be formed. he museum hosted numerous Mexicanand foreign visitors during its irst years, as a result of which some of themexpressed their observations in the Mexico City press. he studied period hasbeen lowly valued by Mexican historiography, which has always consideredthat the museum had a limited institutional and cultural development andthat it was ignored by Mexican society. Nevertheless, literature on press historyfrom the irst half of the 19th century has played a secondary role in thehistorical studies on this institution, although these bibliographies addressquestions on the public life of the National Museum.
Keywords: museum; press; natural history; archeology; history